THE Mad MIssion of Jasmin .j - Jon Blake (London Hodder Children's, 2004)
The last time Jasmin saw Dorothy Wordsearch, the awful author was being eaten by a monster. So how come she's still writing stories? It's time for Jasmin to investigate with the help by her hyper sidekick Kevin Shilling. And when Kevin is won over by a sinister new enemy, Jasmin will need all her wits to save him from a terrible fate. Suggested level: primary, intermediate